The diatom Lindavia intermedia identified as the producer of nuisance pelagic mucilage in lakes. Issue 4 (2nd October 2017) - Novis, Phil; Schallenberg, Marc; Saulnier-Talbot, Émilie; Kilroy, Cathy; Reid, Michael
ABSTRACT: Populations of a centric diatom that produces copious extracellular polymeric substance (EPS), known as 'lake snow', have developed in several large microtrophic lakes in New Zealand over the past 10 years. The EPS coats fishing lines and blocks water filters. The phenomenon was first noticed in Lake Wanaka in the early 2000s and has recently been reported in Lakes Coleridge and Wakatipu, with single, isolated historical events occurring in Lakes Waikaremoana (confirmed) and Benmore (presumed). The species has been reported from a handful of other lakes in New Zealand, all except one of which are microtrophic-to-oligotrophic. Light and ultrastructural microscopic studies of New Zealand populations, DNA sequencing and comparison with published descriptions identify the causative species as Lindavia intermedia, part of the 'bodanicoid' complex. These species are best known from the Northern Hemisphere where they are regarded as confined to nutrient-poor habitats, frequently having disappeared from European lakes as the lakes underwent eutrophication. Lake snow is known from a small number of other lakes in the Northern Hemisphere, but no evidence has been reported linking L. intermedia to the production of lake snow in these lakes. The expected growth characteristics (slow and at depth) of L. intermedia pose difficulties for any prospective containment campaign.